"Living Letterforms": The Ecological Turn in Contemporary Digital Poetics. - RALEY, RITA (Contemporary Literature)
The article discusses the shift of digital poetics to ecological system which combines humans and computational media. It explores the role of technological innovations and modern media environments in the advent of hybrid poetry. It analyzes the combination of digital technology, concrete poetry, cinema, photography and print in the works of artist David Jhave Johnston. It also addresses some of the hindrances to understanding and interpreting digital poetry.